Health Status Measurement Instruments in Chronic Obstructive Pulmonary Disease - Yves Lacasse; Eric Wong; Gordon Guyatt; Roger S Goldstein (Canadian Respiratory Journal)
Chronic obstructive pulmonary disease (COPD) is associated with primary respiratory impairment, disability and handicap, as well as with secondary impairments not necessarily confined to the respiratory system. Because the primary goals of managing patients with COPD include relief of dyspnea and the improvement of health-related quality of life (HRQL), a direct measurement of HRQL is important. Fourteen disease-specific and nine generic questionnaires (four health profiles and five utility measures) most commonly used to measure health status in patients with COPD were reviewed. The measures were classified according to their domain of interest, and their measurement properties - specifications, validity, reliability, responsiveness and interpretability - were described. This review suggests several findings. Currently used health status instruments usually refer to the patients’ perception of performance in three major domains of HRQL - somatic sensation, physical and occupational function, and psychological state. The choice of a questionnaire must be related to its purpose, with a clear distinction being made between its evaluative and discriminative function. In their evaluative function, only a few instruments fulfilled the criteria of responsiveness, and the interpretability of most questionnaires is limited. Generic questionnaires should not be used alone in clinical trials as evaluative instruments because of their inability to detect change over time. Further validation and improved interpretability of existing instruments would be of greater benefit to clinicians and scientists than the development of new questionnaires.